Respon Pertumbuhan Vegetatif Tanaman Kedelai (Gylcine max L.) Terhadap Tingkat Naungan yang Alami - Rista Sanah; Rahmadina Rahmadina (BIOEDUSAINS:Jurnal Pendidikan Biologi dan Sains, 2024)
This research aims to determine the most effective growth response and shade level for vegetative growth of soybeans (Glycine max L.). The experimental design used was a Completely Randomized Design (CRD). ) with 2 factorials, namely factor I, namely N0: Control; N1 : 55%; N2: 65%; N3: 75%; and factor II, namely M1: soil + husks; M2: soil + cocopeat. The results showed that 55% shade (N1) had a significant effect on plant height and number of leaves, 75% shade (N3) had a significant effect on leaf area index, M2 (soil + cocopeat) had a significant effect on plant height, number of leaves and area index. leaf. In conclusion, the growth response of soybean plants to natural shade shows significant growth in plant height, number of leaves, leaf area index and level of shade. The most effective is N1 which has a significant effect on plant height and number of leaves. Apart from that, there are recommendations for choosing a more appropriate media for soybean plants so that their growth and development is more realistic. Keywords: Gylcine max L., Soybeans, Cultivars, Shade, Growth